Cooperative Learning Strategies and Students’ Achievement in Peace Education Concepts of Social Studies in Lagos State, Nigeria - Sunday Oyerinde Fabode; Timilehin Olayinka Omoniyi (International Journal of Social Learning (IJSL), 2026)
The study examined the effects of Graffiti, Jigsaw, and Group Investigation Cooperative Learning Strategies on junior secondary school students’ achievement in peace education in Lagos State, Nigeria, and explored the moderating role of gender. A pretest–posttest quasi-experimental 4×2×2 factorial design was used. A total of 285 students from eight schools were selected. The Peace Education Achievement Test (r = 0.89) and instructional guides were used over a 12-week intervention. Data were analysed using ANCOVA and Scheffé post-hoc tests at 0.05 significance. There was a significant main effect of treatment (F(3,267)=7.16; partial η² = 0.07). Group Investigation produced the highest performance, followed by Jigsaw and Graffiti. Gender and interaction effects were not significant. Cooperative learning strategies improve achievement in peace education and should be integrated into teaching practice. Social studies teachers and curriculum planners should integrate GICLS, JCLS, and GCLS into instructional practice to strengthen peace education outcomes.